Thermochemical Characterization of Rice Husk (Oryza Sativa Linn) for Power Generation - Nikdalila Radenahmad; Md Sumon Reza; Muhammad S. Abu Bakar; Abul K. Azad (ASEAN Journal of Chemical Engineering, 2020)
Rice husk is biomass that can be utilized as fuel for biomass gasification as a renewable energy source. In this paper, thermochemical methods were used to determine the higher heating values, moisture content, bulk density, pellet density, microstructure, and elemental composition of Thai Rice Husk (Oryza Sativa Linn). The heating energy was analyzed using a bomb calorimeter, which showed a higher heating value of 15.46 MJ/kg. Determination of pellet density through rice husk powder pelletization exhibited a value of 1.028 g/cm3, while moisture content was 5.017 wt%. The heating value and moisture content revealed good agreement with the literature values, indicating the potentiality of rice hush for energy generation. Scanning electron microscopy (SEM) showed that the raw rice husk and its ash have similar porosity types but different bulk structure.  Elemental analysis using energy dispersive X-ray (EDX) indicated that rice husk contains O, Si, C while O and C percentages were drastically decreased during combustion. The obtained heating value and moisture content proved that rice husk could be used as a bio-energy source in biomass gasification for power generation.